Bridging the digital divide : effort towards establishing the real impact of information technology to the rural community / Roshidi Hassan and Megat Zuhairy Megat Tajuddin - Hassan, Roshidi; Megat Tajuddin, Megat Zuhairy (Research Management Institute (RMI), 2010)
The Bridging Digital Divide (BDD) Program initiated by the Malaysian government in 1999 has successfully introduced the Information Technology (IT) to the rural communities particularly in Malaysia. The computers and internet connections are available almost at every part ofMalaysia including those in the remote areas. However; to have a real impact of technology on people slives, the effort has to go beyond the infrastructures and technology literacy programs and awareness. Having information available suit to the needs of the local community will bring greater impact ofthe technology to them. Nevertheless, the new approaches need to be introduced to make the effort less costly. Some of the Digital Divide programs require proper coordination with other projects. Coordination with the responsible agencies in providing power utilities and road infrastructures is essential to make such expensive digital divide program more cost effective·and give greater impact to the community. Thus, this paper will provide numerous suggestions on the improvement in providing greater benefits; both the users and the project implementers. Besides, this paper will also discuss on the need of local content in local language with self-sustained nature. lt further highlights the importanceof having basic infrastructure such as electricity and road accessibility that may have influence over the success of BDD program.